Is environmental sustainability a case of failure of policy implementation? - FADWA CHALFOUN (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: The study’s goals were to ascertain the causes of policy implementation failure, the results of that failure on sustainability, and the solutions available for bringing that sustainability.Method: Methodologically, this study employed a quantitative systematic literature review in accordance with the procedures described by Pickering and Byrne.Findings: The systematic review of the literature confirms that issues with communication, politics, and economics are to blame for environmental policies failing to produce the desired results. These results also show how much of a growing concern the failure of environmental policies is.Implications/Novel Contribution: According to the findings, a lack of incentives to adopt environmental policies, poor communication of goals to key stakeholders, and a conflict between the roles of environmental policies and objectives focused on economic development are the main causes of the inability to achieve environmental sustainability. Because of this, policymakers must gain knowledge from these failures if they hope to lead the world to sustainable development.